2003
DOI: 10.3349/ymj.2003.44.1.81
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Critical Pathway for Inguinal Hernia Repair

Abstract: This study was conducted to develop a case management program using the critical pathway (CP) as an intervention method for patients with an inguinal hernia for a herniorrhaphy, and to determine the effects of the CP on the period of hospitalization, medical costs, the rates of postoperative complaints, patient satisfaction and the nurses' job satisfaction. One hundred patients (60 in the experimental group, 40 in the control group) who were admitted to a general hospital in Seoul for inguinal herniorrhaphy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…A recent systematic review indicated that clinical pathways are associated with reductions in hospital length of stay and costs. [26][27][28] A recent study suggested nurses had a greater than expected impact on the success of clinical pathway implementation. Implementation of a clinical pathway in Singapore significantly reduced the length of stay from 3.3 to 1.9 days (P < .001) and hospital charges from S$3929 to S$3524 (P 5 .003).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review indicated that clinical pathways are associated with reductions in hospital length of stay and costs. [26][27][28] A recent study suggested nurses had a greater than expected impact on the success of clinical pathway implementation. Implementation of a clinical pathway in Singapore significantly reduced the length of stay from 3.3 to 1.9 days (P < .001) and hospital charges from S$3929 to S$3524 (P 5 .003).…”
Section: Discussionmentioning
confidence: 99%
“…We choose for the consensus method because of the variety of meanings of the different terms. We decided to delete the term measurement, as defined by Joh (Joh et al. 2003), because its meaning in this context was confusing and ambiguous.…”
Section: Methodsmentioning
confidence: 99%
“…The study failed to demonstrate any significant effect between staff in whose ward the Pathway was introduced and those where this was not the case. Due to a low number of interviewed staff, however, the power of the study was low [20]. A small pilot study assessing the implementation of Clinical Pathways in vascular surgery showed that staff in general had a positive attitude towards the project and found that they were useful for training, for a more collective work and for patient-clinician communication.…”
Section: Staff Satisfactionmentioning
confidence: 96%
“…The effects of Clinical Pathways on patients' satisfaction have not been extensively explored, but there are some studies providing pertinent evidence. Comparisons between pre-and post-pathway care yielded significant increases in patients' satisfaction for colon resections [14] and caesarean sections [40] and a non-significant increase for inguinal hernia repair [20]. Other studies assessed patients' satisfaction after Clinical Pathway introduction without using a comparison group of pre-pathway patients.…”
Section: Patients' Satisfaction With the Hospital Staymentioning
confidence: 97%
See 1 more Smart Citation